METHODOLOGY FOR VARIANT AND GENERATIVE DESIGN OF MICROCOMPONENTS BASED ON THE CAD SYSTEM "MICROSYS 25" (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Microsystems engineering (MSE) is becoming increasingly important for the future technical and economic development of the world. The global market for microsystems products is experiencing tremendous growth, with countries such as the USA, Japan and Germany reaching high levels of development and technological development. It is currently a strategic direction that determines the development of human civilization and completely changes the appearance of manufactured products in the 21st century. Microengineering concerns technolo-gies and the practical implementation of three-dimensional structures and elements based on them with dimensions in the order of micrometers (μm). One of its main goals is to integrate microelectronic circuitry with micromechanical three-dimensional structures, by implementing complex integrated complexes called microsystems (MS). The purpose of this report is to present the developed methodology for variant and generative design of the specialized automated system for designing products from Microsystems Engineering "MICROSYS 25". The developed standard technolo-gical process for the production of flat circular membranes with double-sided plugs, by double-sided anisotropic etching, is illustrated. The recording of the generated information and a standard technological process in the relational database of an automated system is presented. The further development of the "MICROSYS 25" project is the development of multiple technological processes for micromechanical elements and components and their recording in the library database and thus optimizing the process of developing new technological processes.